Perlawanan Tokoh Muhammad Ibnu Qosim terhadap Raja Daher dalam Film Alfaris Wal Amira Kajian Strukturalisme - Nuryadi, Bagja Ghali; Akmaliyah, Akmaliyah; Rohanda, Rohanda (Universitas Lampung, 2025)
This study aims to analyze the story structure in the plot and the characters played by the characters in the film Alfaris Wal Amira (الفارس و الأميرة) by Bashir El Dik. The approach used in dissecting this film is the hero's journey approach by Christopher Vogler to find out the story structure and the archetype approach by Christopher Vogler to find out the characters. This research is a qualitative descriptive research that uses dialogue and cut scenes as data to analyze the film. The data collection technique uses the Simak method by watching repeatedly. The results of this study found that the patterns that occur in the story are not in accordance with those described by Christopher Vogler, the call to the adventure occurs twice before and after the ordinary world. Then Muhammad Ibnu Qosim must go through the second threshold after the road back before the resurrection. Archetype the tricker is played by two characters, the pirate who is the right hand of King Daher and the witch.Keywords: Movie, Hero's Journey, Archetype, Christopher Vogler